Prevalence of unintended pregnancy among antenatal care followers, in kersa woreda, estern hararghae, Ethiopia - Gebremedhin, Merhawi; Gebrehawerya, Tewelde; Tesfaye, Gezahagn; Alemayehu, Mariam; Waritu, Sultan (International Journal of Medicine, 2017)
Introduction: Unintended pregnancy is an important Public health concern worldwide that affect women, families and society at large. An unintended pregnancy has been responsible for unplanned and mostly unwanted family unions that ultimately cause disrupted lifestyles, a source of conflict between individuals and families as well as discrimination against girl hence the objective of this study was aimed to assess the prevalence of unintended pregnancy and its cause among ANC followers.Methodology: The study was conducted in kersa woreda, Eastern hararghae, Ethiopia from February to March, 2015. Facility based descriptive cross-sectional study was conducted among the sample of pregnant women visiting the randomly selected health facility. The source population was all pregnant women residing in kersa woreda and the study population was all pregnant women found in study area who visited health institution for ANC follow up. Our sample was 328 women, and respondents were selected using systematic random sampling. The data was cleaned, entered and analyzed using SPSS version 20.0.Result: The magnitude of unintended pregnancy was 31.3% of those, 82(25.6%) was mistimed and 18 (5.6%) was unwanted. Decision power, no radio, and not able to discuss with partner showed significant association. God’s order, husband contraceptive disapproval, and lack of information on contraceptives were mentioned as main cause for current unintended pregnancy.Conclusion: unintended pregnancy was prevalent in 31.3%. Absence of radio, lack of information and lack of discussion with partner was significant predictors. Health information dissemination is needed to community residents, and local governors should ensure that accessible, affordable and acceptable contraceptive is in place.